Pendidikan Karakter dan Pembangunan Sumber Daya Manusia Keberlanjutan - Sri Suwartini (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2017)
Abstract: Character education is a system of inculcating the character of knowledge, awareness or willingness, and actions to implement those values. Character education is believed to be an important aspect in the improvement of human resources (HR), as it contributes to the development of a community. The character of a qualified society needs to be established and nurtured from an early age, because early age is a "golden" but critical for the formation of one's character. Implementation of character education is felt very urgent implemented in order to nurture the younger generation of the nation. National education aims to develop the Almighty, have a noble character, healthy, knowledgeable, capable, creative, independent, and become citizens of a democratic and responsible. In relation to character education, the Indonesian nation is in great need of human resources (human resources) large and qualified to support the implementation of development programs properly. Quality education, which can support the achievement of the nation's ideals in having quality resources. Strongly characterized HR is characterized by different mental capacities with others such as trustworthiness, sincerity, honesty, courage, firmness, firmness, strength in principle, and other unique qualities inherent in itself. The character of a nation will be closely linked to the achievements of the nation itself in various life. Character formation is developed through the stage of knowledge (knowing), implementation (acting), and habits (habit).